The Role of Cocurricular Activities in Developing Students' 4C Skills in the Implementation of the Independent Curriculum - Sinaga, Prilchilia Padya; Lasmawan, I Wayan; Budiarta, I Wayan (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
The implementation of the Independent Curriculum emphasizes the development of 21st-century competencies known as the 4C skills: critical thinking, creativity, communication, and collaboration. These skills can be strengthened through co-curricular activities as a form of contextual learning outside of extracurricular activities. This study aims to describe the role of co-curricular activities in developing students' 4C skills during the implementation of the Independent Curriculum at SMA Negeri 1 Banjar. The study used a qualitative approach with descriptive methods. The research subjects included students, co-curricular activity supervisors, and school officials. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that co-curricular activities were able to provide meaningful learning experiences that supported the development of students' critical thinking, creativity, communication, and collaboration skills. Before the co-curricular activities were optimally implemented, students tended to be passive and lacked confidence in expressing their opinions. However, after the implementation of co-curricular activities based on direct experience, students' social and academic skills improved. Thus, co-curricular activities have a strategic role in supporting the successful implementation of the Independent Curriculum by strengthening students' 4C skills. Keywords: Co-curricular Activities, 4C Skills, Independent Curriculum, 21st Century Learning